Laparoscopic assisted vaginal hysterectomy: an experience at a Fortis Escorts hospital - Rajput, Neelu; Yadav, Sahab Singh; Narwade, Pratibha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to evaluate the laparoscopic assisted vaginal hysterectomy (LAVH) in terms of demographic data of patients, indications, uterine size, intraoperative and postoperative complications, amount of blood loss, operative time and duration of hospital stay. Methods: A retrospective study was conducted on 160 cases, who underwent laparoscopic assisted vaginal hysterectomy in the period between October 2018 to November 2019 at the Fortis Escorts Hospital, Faridabad, Haryana, India. Results: Majority of patients (58.75%) belongs to age group between 40-50 year. Only 30.62% cases had a history of one previous abdomino-pelvic surgery. Majority of cases (52.5%) in the study group had uterine size between 6-12 weeks. Most common indication of hysterectomy in this study was fibroid uterus which account for 49.37% of cases followed by dysfunctional uterine bleeding (16.87%) cases. Mean time of surgery in this study was 114.4±0.59 min and average blood loss was 135.62±47.63 ml. The mean weight of uterus was 243.75±82.94 gm. 5% cases had major intraoperative complications while minor postoperative complications were seen in 16.87% cases. Bladder injury was seen in 1.25%. Major haemorrhage occur in 1.25%. In this study conversion to laparotomy rate was 1.25%. Only one case of ureteric injury and one case of bowel injury was noted. Among minor complications fever (6.25%) and urinary tract infection (5.62%) were mainly seen. Mean duration of hospital stay was 2.82±1.17 days. Conclusions: LAVH enables the surgeon to convert most of the abdominal hysterectomies into vaginal ones and hence decreases postoperative pain, decreases complications, lesser duration of hospital stay and rapid return to normal activity.